Religious Education and Local Policy: Lessons from the Al-Qur’an Literacy Program in Prabumulih - Akhmad Muftizar; Muhammad Sirozi; Karoma Karoma (AL-ISHLAH: Jurnal Pendidikan, 2025)
Local religious education policies in Indonesia are increasingly shaped by the intersection of community aspirations, governance, and political interests. Prabumulih Mayor Regulation No. 42 of 2016, mandating Al-Qur’an reading and writing (BTQ), represents a key case of how religious education is institutionalized within local public policy. This study employed a qualitative case study approach involving in-depth interviews, observations, and document analysis. A total of 24 informants were selected, including government officials, religious leaders, educators, and parents. Data were analyzed using the Miles and Huberman interactive model and validated through source triangulation. Findings indicate that the BTQ policy implementation involves multi-actor governance, including the Education Office, Ministry of Religious Affairs, schools, religious organizations, and the media. The policy is integrated into the school curriculum and functions as both an educational mandate and a political tool. Structural constraints such as teacher shortages, weak parental involvement, and unequal access to learning resources hinder optimal implementation. The BTQ program reflects a convergence of educational, religious, and political agendas. While it enhances Al-Qur’an literacy and student character development, it also serves as a vehicle for political legitimacy in a religiously driven society. The study highlights the importance of collaborative governance and contextual responsiveness in religious education policy.